The Terrorist's Dilemma : Managing Violent Covert Organizations - Shapiro, Jacob N. (Princeton University Press, 2013)
How do terrorist groups control their members? Do the tools groups use to monitor their operatives and enforce discipline create security vulnerabilities that governments can exploit? The Terrorist's Dilemma is the first book to systematically examine the great variation in how terrorist groups are structured. Employing a broad range of agency theory, historical case studies, and terrorists' own internal documents, Jacob Shapiro provocatively discusses the core managerial challenges that terrorists face and illustrates how their political goals interact with the operational environment.